Civil society takes the wheel: UNSC resolution 1325 and the path towards sustainable peace - Dias, Mónica (2020)
Resolution 1325’s contribution to a more sustainable peace is now widely recognized, not only in post-conflict settings, but also in preventing violence, in various forms, in contexts of immanent or latent conflict. One of the most important factors for the Resolution’s success lies in its influence on civil society, but also in the impact that civil society itself has on the application and operationalization of this Resolution, revealing the gender perspective as essential and generating a dynamic of very fertile reciprocity for the possibility of peace. In the article, we will analyze the impelling action of civil society for the affirmation of women as central actors in peace processes - as well as in the political, social, economic and cultural reconstruction that follows. Through several examples and suggestions, we will see how this dynamic for sustainable peace was reinforced and expanded through the Sustainable Development Goals and the special place reserved there for women.